A new Colombian species of Cryptocellus (Arachnida, Ricinulei), with notes on the taxonomy of the genus - Botero-Trujillo, Ricardo (Zootaxa, 2014)
Cryptocellus sofiae sp. nov. is described based on males and females obtained from the easternmost part of Colombia, in Vichada Department. The new species is placed in the adisi species-group, based on the morphology of the male copulatory apparatus and the presence of polygonal (navicular or calyx-like) setae. With this addition, the group now comprises four species. A key for the identification of the members of this group is provided. Some taxonomic remarks about the adisi group and the genus Cryptocellus Westwood, 1874 are made.